Bak Thai restaurant / Izwan Zainuddin, Wan Mohd Rasman and Mohd Ezylin Yazed - Izwan, Zainuddin; Wan Mohd Rasman, Wan; Mohd Ezylin, Yazed (Faculty of Hotel and Tourism Management, 2003)
Bak Thai is the name of our company after all shareholders in the company agreed with it. We serve customer Bak Thai foods as well as providing them entertainment like as well as watching and listening to music videos or songs. Not only the customer will have a good time at our restaurant, they will be served with the most Bak Thai delicious. There is no restaurant that serves Thai food in Damansara Perdana. We don't have competitors from the same kind of product but we have competitors from the Western Cuisine like Pizza Hut, Me' Donald's, and KFC. They use foods as their main business. Bak Thai is the answer to an increasing demand of the public. We at Bak Thai believe and trust that the people want to change their taste of foods. They are Italian foods, American foods but not Thai foods. We have a very good deal for couple, family or friends. They will have a very good time at our restaurant. We are situated at Perdana Business Centre.